2007
DOI: 10.1002/app.26719
|View full text |Cite
|
Sign up to set email alerts
|

Dyeable polypropylene fibers via nanotechnology

Abstract: Polypropylene (PP) nanocomposites with three different clay loadings were prepared by solution mixing technique. The solution-mixed nanocomposites were extruded to fibers using a single screw extruder. The PP nanocomposite fibers obtained were uniformly dyed with three distinct disperse dyes at different levels of shade. The enhanced dyeability of PP nanocomposite fibers was characterized by spectrophotometric measurements. Satisfactory wash, light and crock fastness results were also achieved. Mechanical prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 8 publications
1
43
0
1
Order By: Relevance
“…However, to solve the mentioned problem numerous attempts have been carried out to modify polypropylene to make it dyeable from aqueous liquor at atmospheric condition through various approaches such as gamma radiation (Kaur and Misra, 1987), chemical oxidation treatment and functionalization (Tehrani Bagha et al, 2004;Choi and Park, 2008), plasma treatment (Klein et al, 2000;Yaman et al, 2009), graft copolymerization (Bhattacharya and Inamdar, 2007;Jang and Go, 2008), and producing the dyeable alloy fibers by polymer blending processes (Marcincin et al, 2000;Prchal et al, 1997;Kotek et al, 2004;Huang et al, 2005;Yu et al, 2007;Teli et al, 2004). Some recent researches for preparation of dyeable PP fibers devoted to low molecular weight compounds and nanoparticles (Toshniwal et al, 2007;Yu et al, 2009), dendrimers (Froehling and Burkinshaw, 2001) and hyperbranched polymers (Burkinshaw et al, 2002). Considering industrial, effectual and economical aspects, among mentioned methods to improve the dyeablity of PP fibers, recently producing dyeable alloy PP fibers have been paid more attention.…”
Section: Introductionmentioning
confidence: 97%
“…However, to solve the mentioned problem numerous attempts have been carried out to modify polypropylene to make it dyeable from aqueous liquor at atmospheric condition through various approaches such as gamma radiation (Kaur and Misra, 1987), chemical oxidation treatment and functionalization (Tehrani Bagha et al, 2004;Choi and Park, 2008), plasma treatment (Klein et al, 2000;Yaman et al, 2009), graft copolymerization (Bhattacharya and Inamdar, 2007;Jang and Go, 2008), and producing the dyeable alloy fibers by polymer blending processes (Marcincin et al, 2000;Prchal et al, 1997;Kotek et al, 2004;Huang et al, 2005;Yu et al, 2007;Teli et al, 2004). Some recent researches for preparation of dyeable PP fibers devoted to low molecular weight compounds and nanoparticles (Toshniwal et al, 2007;Yu et al, 2009), dendrimers (Froehling and Burkinshaw, 2001) and hyperbranched polymers (Burkinshaw et al, 2002). Considering industrial, effectual and economical aspects, among mentioned methods to improve the dyeablity of PP fibers, recently producing dyeable alloy PP fibers have been paid more attention.…”
Section: Introductionmentioning
confidence: 97%
“…Blending of polymeric fibers with nanoclays as inexpensive materials is still claimed as cost effective method to enhance dyeability (Geoghegan & Krausch, 2003). Up to now, only two research articles are focused on dyeing properties of polypropylene-and polyamide 6-layered clay incorporated nanocomposites prepared by melt compounding (Razafimahefa et al, 2005;Toshniwal et al, 2007). Toshniwal et al suggested that polypropylene fibers could be made dyeable with disperse dyes by addition of nanoclay particles in polymer matrix (Toshniwal et al, 2007).…”
Section: Bulk Modification Of Synthetic Textiles Using Nanomaterialsmentioning
confidence: 99%
“…Up to now, only two research articles are focused on dyeing properties of polypropylene-and polyamide 6-layered clay incorporated nanocomposites prepared by melt compounding (Razafimahefa et al, 2005;Toshniwal et al, 2007). Toshniwal et al suggested that polypropylene fibers could be made dyeable with disperse dyes by addition of nanoclay particles in polymer matrix (Toshniwal et al, 2007). Another research work done by Razafimahefa and her colleagues showed that the introduction of the nanoclay improves the dyeing ability of nylon with disperse dyes.…”
Section: Bulk Modification Of Synthetic Textiles Using Nanomaterialsmentioning
confidence: 99%
“…It has been reported that dyeability of polypropylene fiber can be improved by blending with polar polymers (Asiaban & Moradian, 2011Bolhova, Ujhelyiova, Valkova, & Marcincin, 2007;Mirjalili, Moradian, & Ameri, 2011Razafimahefa, Chlebicki, Vroman, & Devaux, 2005Toshniwal, Fan, & Ugbolue, 2007;Ujhelyiova, Bolhova, Oravkinova, Tiňo, & Marcinčin, 2007). Kotek, Afshari, Gupta, Kish, and Jung (2003) indicated that the dye uptake of PP/PA6 blend fibers depends on a number of factors, including the proportion of components and porosity of the fibers.…”
Section: Introductionmentioning
confidence: 97%